Introspecting Queer Identities in Mainstream Indian Regional Cinema - K., Karthik; Deepthi, Deepthi (Journal of Research in Social Science and Humanities, 2025)
The public notion across cultures in most societies has always thrived largely towards Hetero Sexuality. Historically, around the world, there is a general tendency to showcase intolerance towards sexual minorities such as lesbian, gay, bisexual, and transgender (LGBT) and identify them as people with abnormalities. In India, talking about people with varied sexual identities and orientations is still considered to be taboo. Their voices and concerns are often unheard or unattended, and they remain underrepresented in the mainstream media.  Such communities deserve a space for public discourse so that their voices are heard in a more sensitive manner. The representation of sexual minorities in Indian cinema has often historically been stereotyped, which denies them from getting acceptance in a given society. However, there are attempts to explore the themes of sexual minorities and their concerns in South Indian Cinema. Hence, it is important to study such portrayals and understand how the industry is slowly embracing the community through its narratives. In this context, the study aims to examine the construction and representation of Homosexuality in two selected Malayalam films, Moothan (2019) and The Kaathal - the Core (2023). Using a queer theoretical framework,  the study further traces the emotional complexities of homosexual characters portrayed in these films. Eventually, it evaluates how these films voice homosexuals and helps to create a positive perspective about homosexuality among its viewers.